2010
DOI: 10.1103/physrevc.81.054303
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of random two-body interactions

Abstract: The input to the configuration-interaction shell model includes many dozens or hundreds of independent two-body matrix elements. Previous studies have shown that when fitting to experimental low-lying spectra, the greatest sensitivity is to only a few linear combinations of matrix elements.Here we consider interactions drawn from the two-body random ensemble, or TBRE, and find that the low-lying spectra are also most sensitive to only a few linear combinations of two-body matrix elements, in a fashion nearly i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In the fit they found that about five or six linear combinations of parameters were the most important. (Interesting, a similar result was found for random values of the matrix elements [19]).…”
Section: Introductionsupporting
confidence: 76%
“…In the fit they found that about five or six linear combinations of parameters were the most important. (Interesting, a similar result was found for random values of the matrix elements [19]).…”
Section: Introductionsupporting
confidence: 76%
“…[34][35][36][37]), in nuclear physics we are just starting to explore such ideas in many-body calculations. However, there have been a variety of attempts to employ factorization techniques in fitting procedures or as diagnostic tools [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%